Long-term Well-being Among Survivors of the Rwandan and Cambodian Genocides - Milazzo, Annamaria (Taylor and Francis, 2021)
This paper adds to the thin empirical literature estimating the long-term effects of exposure to conflict from in utero to adolescence on adult well-being. The effects through adolescence of the two worst genocides in recent history—those occurring in Rwanda (1994) and Cambodia (1975–79)—are examined. The Rwandan genocide is shown to have produced long-term health outcomes among women exposed to the conflict during adolescence. A further contribution is the analysis of gendered effects during adolescence, which is enabled by the availability of data on men’s height for Rwanda. The long-term effects are confirmed for men, however this appears to be the consequence of exposure during adolescence later than for women, a result that is consistent with the biological literature on the differential timing of the onset of puberty by gender. No significant effects are detected in the case of the Cambodian genocide and we discuss some issues that may influence this result. Although more research and better data are needed, our results are suggestive of adolescent-specific effects of the Rwandan genocide, which may be comparable or larger than those previously found for younger children.